2016
DOI: 10.1088/1748-9326/11/10/104008
|View full text |Cite
|
Sign up to set email alerts
|

Global warming induced hybrid rainy seasons in the Sahel

Abstract: The small rainfall recovery observed over the Sahel, concomitant with a regional climate warming, conceals some drought features that exacerbate food security. The new rainfall features include false start and early cessation of rainy seasons, increased frequency of intense daily rainfall, increasing number of hot nights and warm days and a decreasing trend in diurnal temperature range. Here, we explain these mixed dry/wet seasonal rainfall features which are called hybrid rainy seasons by delving into observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 29 publications
3
53
0
2
Order By: Relevance
“…This relationship between DTR, rainy days and rainfall amount makes DTR anomalies useful to detect drought flags in the Sahel as discussed by Salack et al . (). The results on the increase in the number of warm days and the reduction of cool nights are similar to the observations made by Ly et al .…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This relationship between DTR, rainy days and rainfall amount makes DTR anomalies useful to detect drought flags in the Sahel as discussed by Salack et al . (). The results on the increase in the number of warm days and the reduction of cool nights are similar to the observations made by Ly et al .…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…Rainfall has returned slightly relative to the 1980s drought conditions (Lebel and Ali, 2009), with some high variability of extreme events (Ly et al, 2013;Salack et al, 2016;Taylor et al, 2017;Salack et al, 2018). There are indications that farmers' management of land and agroforestry through natural regeneration is also achieving success by ingeniously modifying traditional agroforestry, water and soil-management practices (IFPRI, 2009).…”
Section: The Sahel Greenbelt Scenariomentioning
confidence: 99%
“…The dynamics of the WAM system are a consequence of complex interactions between dynamics, thermodynamics and surface conditions (Cook, 1999;Flaounas et al, 2012;Nicholson, 2013). In West Africa, where rainfall is limited to only few months per year except for the coastal regions, a correct representation of the WAM circulation and the associated onset and cessation of the rainy season are of utmost interest for farming management (Salack et al, 2016). In recent studies, Mounkaila et al (2015) and Klein et al (2015) showed that the ability of RCMs in simulating onset and cessation of the rainy season over West Africa strongly depends on how 1 http://www.wascal.org, last access: 14 April 2018 well the models reproduce the northward movement of the monsoon system and its associated features.…”
Section: Introductionmentioning
confidence: 99%
“…The work presented here advances the regional downscaling efforts for the region through the generation of a highresolution, ensemble regional climate simulation experiment for large areas of continental West Africa and extensive periods of the 21st century at a horizontal resolution of 12 km. Three GCMs are downscaled using the Weather Research and Forecasting Model (Skamarock et al, 2008) to narrow down uncertainties and provide estimates on the range of climate change impact on the region. A control run using reanalysis data as forcing is added to assess the RCM bias.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of the WAM system are a consequence of complex interactions between dynamics, thermodynamics and surface 25 conditions (Cook, 1999;Flaounas et al, 2012;Nicholson, 2013). In West Africa, where rainfall is limited to only few months per year, a correct representation of the WAM circulation and the associated onset and cessation of the rainy season are of utmost interest for farming management (Salack et al, 2016). In recent studies, Mounkaila et al (2014) and Klein et al (2015) showed that the ability of RCMs in simulating onset and cessation of the rainy season over West Africa strongly depends on how well the models reproduce the northward movement of the monsoon system and its associated features.…”
Section: Introductionmentioning
confidence: 99%